KEMAMPUAN MEMBACA SEKUENSI DAN MEMBACA PEMAHAMAN SISWA KELAS VII SMP DAREL HIKMAH PEKANBARU - Razak, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The tiltle of this research is the Ability of the Eighth Grade Student of SMP Darel Hikmah Pekanbaru in Reading Sequences and Reading Comprehension. The aim of this research is to describe significant difference between reading sequences and reading comprehension of the eighth grade students of SMP Darel Hikmah Pekanbaru. The method used was descriptive method. The data were the scores of the test about reading sequences and reading comprehension of the eighth grade students of SMP Darel Hikmah Pekanbaru which consists of 5 parallel classes with population 130 students and the sample was 99 students. The data collection technique was by distributing tests of reading sequences and reading comprehension. To find out significant difference between reading sequences and reading comprehension for each sample, level of the data, and race, ANOVA was used. If ANOVA was declined, T-test was calculated. Based on the research, the findings were; (1) the ability of reading sequences was low; (2) the ability of reading comprehension was low; (3) the ability of reading sequences and reading comprehension were equal for each sample, it means that there was no difference between the ability of reading sequences and reading comprehension among the eighth students or between one to other classes; (4) the ability of reading sequences and reading comprehension were equal for each level, it means that there was no difference between reading sequences and reading comprehension among the same level of the data (level 1, level 2, and level 3); (5) the ability of reading sequences and reading comprehension were equal for each race, it means that there was no difference between reading sequence and reading comprehension among the same race or between one race to other races. Overall, it can be concluded that the ability of the eighth grade students of SMP Darel Hikmah Pekanbaru in reading sequences and reading comprehension were low which were between 56.00 % - 70.00 %.Keyword: The ability of reading sequences and the ability of reading comprehension